Melanotic neuroectodermal tumour of infancy: Refining the surgical approach. Issue 10 (October 2019) - Rickart, A.J.; Drummond-Hay, V.; Suchak, A.; Sadiq, Z.; Sebire, N.J.; Slater, O.; Mills, C.
Abstract: Melanotic neuroectodermal tumours of infancy (MNTI) are particularly rare and although predominantly benign, are infiltrative and locally aggressive. Presenting in the first year of life, prompt diagnosis and effective management are critical in minimizing morbidity and the risk of recurrence. A retrospective review of 11 MNTI managed at Great Ormond Street Hospital (GOSH) from 2000 to 2017 was undertaken. Eight tumours presented in the maxilla, two in the skull and one in the mandible. The primary modality of treatment was surgery in 10 cases with one patient receiving neoadjuvant chemotherapy. In spite of microscopically incomplete resection in seven cases, only three recurred. Overall, there was a local recurrence rate of 27% with no distant metastases noted. Disease-free survival was 100% with a follow-up ranging from 0.75 to 17 years (median 5 years). Taking our results in conjunction with the available literature, there is a role for conservative initial surgery of MNTI and this should be coupled with delayed reconstruction and intensive short-term follow-up. We propose an adapted treatment algorithm that aims to balance the risk of recurrence and malignant change with surgical morbidity in an infant population.